Reeducación de la marcha en pacientes con trastorno del espectro autista. - Gualli Pomaquiza, Laura Lizbeth (2025)
Introduction: Autism Spectrum Disorder affects social and communicative interaction relating to stereotyped behaviours manifesting with different symptoms and levels of disability. According to the WHO, 1 in 100 children have a diagnosis of ASD; in Ecuador 5,738 cases have been registered. The delayed maturation of the structures of the nervous system causes alterations in social behaviour, language, cognitive functions, etc. Gait is a locomotion process regulated by the visual, vestibular and proprioceptive systems through efferents, afferents, medulla, brain stem, cerebellum and cerebral hemispheres. Theoretical framework: Eugen Bleuler coined the term autism in relation to schizophrenia, but over the years it was identified as ASD according to the DSM5. Its aetiology is not clear, it is associated with environmental factors and defects in the metallothionein protein. The alteration in the nervous system affects the phases and sapciotemporal variables of gait. Objective: To determine physiotherapeutic treatments used for gait re-education in people with autism spectrum disorder through a literature review. Methodology: A search for randomised controlled studies and case studies was carried out in databases and scientific journals applying inclusion and exclusion criteria. Results: 45 randomised controlled studies were collected with a final sample of 14; 34 case studies were collected with a final sample of 6. Conclusions: Physiotherapeutic treatments with sensory stimuli benefit gait re-education, but symptomatic variability influences treatment time.